Building the nation through efficiency of waqf institutions - Husin, Azrizal; Ismail, Shafinar; Bakri, Mohammed Hariri (Penerbit UTeM Press, 2023)
This book aims to explore the efficiency of Waqf institutions in Malaysia. In recent years, there has been growing attention to the role of Waqf institutions in the Muslim world. The book presents a comprehensive analysis of the current state of and recommendations for improving their efficiency.